Surface Modification Techniques for Biomedical Grade of Titanium Alloys: Oxidation, Carburization and Ion Implantation Processes - Izman, S.; Abdul-Kadir, Mohammed Rafiq; Anwar, Mahmood; Nazim, E.M.; Rosliza, R.; Shah, A.; Hassan, M.A. (IntechOpen, 2012)
None